Bibliometric analysis of competency of specialist nurses based on CiteSpace (基于CiteSpace的专科护士胜任力的文献计量学分析) - LI Xingxing (李星星); WU Lili (吴莉莉); LIANG Ju (梁菊); ZHAO Xin (赵歆); LI Wenqin (李文琴); XUAN Ping (宣萍) (中西医结合护理)
Objective To explore the research hotspots and frontiers of competency of specialist nurses in recent 20 years. Methods The bibliometric software of CiteSpace was used to analyze the publication trends, authors and institutions of publications and to draw keyword clustering map on competency of specialist nurses from China National Knowledge Infrastructure (CNKI) and Web of Science database. Results A total of 1095 articles in CNKI database and 864 articles in Web of Science database were included. The bibliometric results showed that the common research hotspots of Chinese and foreign literatures were the influencing factors of specialist nurse competency, the evaluation index of specialist nurse competency and the training of specialist nurse competency. Conclusion The research focus of foreign literature is wider and deeper than that of Chinese literature, and there is still a certain gap between foreign literature and high-quality literature. Future researchers may learn from foreign literature, further expand and refine the research content, and improve the quality of research evidence. (目的 探讨近20年专科护士胜任力研究热点及研究前沿。方法 运用CiteSpace文献计量软件, 分析中国知网(CNKI)及Web of Science数据库收录的专科护士胜任力相关文献的发文分布趋势、发文作者及发文机构, 绘制关键词聚类图谱。结果 共纳入CNKI 数据库文献1095篇, Web of Science 数据库文献864篇。文献计量结果显示, 中外文献共同的研究热点为专科护士胜任力的影响因素、专科护士胜任力的评价指标以及专科护士胜任力的培训。结论 外文文献的研究热点较中文文献的广泛而深入, 与外文高质量文献仍有一定差距, 未来研究可借鉴外文文献, 进一步将研究内容扩大、细化深入, 提高研究证据质量。)